(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
The fresh water reserves on the earth are finite. The brackish water can be converted tothe fresh water by solar water distillery. A theoretical investigation to investigate the effect ofthe turning hollow-cylinder within the solar still equipped with flat plate solar water collectoron the output of distillate water and its thermal efficiency. The numerical analysis was carriedout by using FORTRAN 90, program. The numerical analysis is used for complex phenomenawithout resorting to expensive prototypes and difficult experimental measurements. The studyconsidered several parameters which are; solar radiation intensity, ambient air temperature,ambient wind velocity, basin plate temperature, basin water temperature, glass covertemperature and hollow cylinder surfaces temperature. The cumulative of distillate wateroutput from the modified solar still increased compared with the conventional solar still by afactor not less than 240%